1998
DOI: 10.1124/mol.53.4.708
|View full text |Cite
|
Sign up to set email alerts
|

Human HistamineN-Methyltransferase Pharmacogenetics: Common Genetic Polymorphisms that Alter Activity

Abstract: Histamine N-methyltransferase (HNMT) catalyzes a major pathway in histamine metabolism. Levels of HNMT activity in humans are regulated by inheritance. We set out to study the molecular basis for this genetic regulation. Northern blot analysis showed that HNMT is highly expressed in the kidney, so we determined levels of enzyme activity and thermal stability in 127 human renal biopsy samples. DNA was isolated from 12 kidney samples with widely different HNMT phenotypes, and exons of the HNMT gene were amplifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
133
1
2

Year Published

2000
2000
2013
2013

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 132 publications
(142 citation statements)
references
References 32 publications
6
133
1
2
Order By: Relevance
“…An earlier study identified the C314T polymorphism as the functional variant within this gene (Preuss et al 1998). This polymorphism has previously been shown to reduce the enzymatic activity (Preuss et al 1998) and to represent a risk for asthma in the Caucasian population (Yan et al 2000a). Yan et al (2000a) found a significant increase in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…An earlier study identified the C314T polymorphism as the functional variant within this gene (Preuss et al 1998). This polymorphism has previously been shown to reduce the enzymatic activity (Preuss et al 1998) and to represent a risk for asthma in the Caucasian population (Yan et al 2000a). Yan et al (2000a) found a significant increase in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In our initial genotyping, the A595G was found to be nonpolymorphic (N=200). Similarly, this variant was also not detected in the study conducted in the Caucasian population (Preuss et al 1998). For the C314T SNP, the distribution of the 314A and 314T alleles was found to be similar in cases and controls (LR v 2 =0.22, d.f.=1, P=0.64).…”
Section: Total Serum Ige Levels In Patients and Healthy Volunteersmentioning
confidence: 89%
See 2 more Smart Citations
“…HNMT is widely expressed in human tissues; the greatest expression is in the liver and kidney, but also in the spleen, colon, prostate, ovary, brain, bronchi, and trachea (Maintz & Novak, 2007). Common genetic polymorphisms for HNMT might be related to a possible role for individual variation in histamine metabolism in the pathophysiology of diseases such as allergy, asthma, peptic ulcer disease, and some neuropsychiatric illnesses (Preuss et al, 1998). Phenylethanolamine N-methyltransferase (PNMT) plays a role in neuroendocrine and blood pressure regulation in the central nervous system.…”
Section: N-methylationmentioning
confidence: 99%